Dietary insulin index and insulin load in relation to hypertriglyceridemic waist phenotype and low brain derived neurotrophic factor in adults - Hajhashemy, Zahra; Lotfi, Keyhan; Shahdadian, Farnaz; Rouhani, Parisa; Heidari, Zahra; Saneei, Parvane (Frontiers in Nutrition, 2022)
Background: The evidence about the relation of the insulinemic potential of food with visceral obesity and brain-derived neurotrophic factor (BDNF) was limited. We aimed to investigate the relation of dietary insulin index (DII) and dietary insulin load (DIL) with hypertriglyceridemic waist phenotype (HTGW) and serum BDNF in Iranian adults. Methods: This cross-sectional study included 528 middle-aged adults (45.6% women), using a multistage cluster random-sampling method. Dietary intakes were assessed using a validated semi-quantitative 168-item food frequency questionnaire. Blood samples were collected after 12 hours of fasting for assessing the serum BDNF and triglyceride concentrations. HTGW was defined as triacylglycerol ≥ 150 mg/dL plus enlarged waist circumference. The values less than the first decile of serum BDNF were considered as the low level. Results: Individuals in the top tertile of DIL, in comparison to those in the bottom tertile, had higher odds of HTGW in both crude (OR=1.96, 95%CI: 1.14-3.37) and fully-adjusted model (OR=6.10, 95%CI: 1.58-23.53). However, the relation between DII and odds of HTGW was statistically insignificant in crude (OR=1.30, 95%CI: 0.78-2.16) and maximally-adjusted model (OR=1.25, 95%CI: 0.65-2.40). After considering confounders, participants in the top tertile of DIL had marginally higher odds of having low BDNF values (OR=2.00, 95%CI: 0.95-4.21). Nevertheless, the association between DII and odds of low BDNF values was statistically insignificant. Conclusions: This population-based study demonstrated that adults with higher DIL had significantly higher chance of HTGW phenotype and slightly higher chance for low BDNF level. DII was not associated with HTGW phenotype or BDNF values.